Hubungan Karakteristik Individu Dengan Kelelahan Kerja Pada Nelayan Tradisional Di Dusun Tanah Merah Kecamatan Huamual Belakang Kabupaten Seram Bagian Barat - Sunik Cahyawati; Sahrir Sillehu; Ira Fanty Wakan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
One of the occupational safety and health (K3) problems that can trigger work accidents is fatigue. Work fatigue is a person's condition where their resilience and efficiency at work decreases. Work fatigue is an important problem to overcome, because work fatigue can cause health conditions to decline which will result in decreased work productivity and work accidents. This study aims to determine the relationship between individual characteristics and work fatigue in traditional fishermen in Tanah Merah Hamlet, Huamual Belakang District, West Seram Regency. This research is quantitative research using a